Challenges in Becoming Female Leaders: Case Study of National and Private University in Indonesia - Dyah Putri Puspitasari; Dedy Sushandoyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The emerging issue of gender equality raise a concern in the professional sector, questioning whether women have the same opportunity in aspiring to be leaders and strive in their career. This paper aims to portray the challenges female employees must face to become a leader. Two prominent business school from high-ranked national and private university in Indonesia are selected as the sample. In-depth interviews with six female leaders from those universities were conducted to gather a broad view on the matter. Result shows that both business schools support female advancement in leadership, hence suggesting that challenges regarding gender are minimal in an academic institution. However, a number of challenges female leaders experienced throughout their journey to a leadership position is concluded through this study, in hope to provide insight to other striving female workers. Although there is a certain belief and some hindrances that hold them from striving forward in their career, they claimed that those are still easy to manage. Based on that finding, practical implications are suggested.